2019
DOI: 10.1186/s12861-019-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transcriptomes of two tardigrades with different hatching coordination

Abstract: BackgroundTardigrades are microscopic organisms, famous for their tolerance against extreme environments. The establishment of rearing systems of multiple species has allowed for comparison of tardigrade physiology, in particular in embryogenesis. Interestingly, in-lab cultures of limnic species showed smaller variation in hatching timing than terrestrial species, suggesting a hatching regulation mechanism acquired by adaptation to their habitat.ResultsTo this end, we screened for coordinated gene expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…This suggests that differences in the photoecology of juvenile and adult tardigrades have driven this opsin divergence within Tardigrada. Prior research in the Tardigrada has also found differential expression of the cryptobiotic response proteins CAHS and SAHS through ontology ( Yoshida et al 2019 ). These orthologs are instrumental in the maintenance of tardigrade desiccation cryptobiosis at all of its life stages, and it is possible that the differential expression of opsin is also linked to this response, considering the common linkage between light intensity and aridity ( Yoshida et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that differences in the photoecology of juvenile and adult tardigrades have driven this opsin divergence within Tardigrada. Prior research in the Tardigrada has also found differential expression of the cryptobiotic response proteins CAHS and SAHS through ontology ( Yoshida et al 2019 ). These orthologs are instrumental in the maintenance of tardigrade desiccation cryptobiosis at all of its life stages, and it is possible that the differential expression of opsin is also linked to this response, considering the common linkage between light intensity and aridity ( Yoshida et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior research in the Tardigrada has also found differential expression of the cryptobiotic response proteins CAHS and SAHS through ontology ( Yoshida et al 2019 ). These orthologs are instrumental in the maintenance of tardigrade desiccation cryptobiosis at all of its life stages, and it is possible that the differential expression of opsin is also linked to this response, considering the common linkage between light intensity and aridity ( Yoshida et al 2019 ). Notably, Hypsibius c-opsin 3 showed no signs of differential expression across the organism’s ontogeny.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lab culture methods have been developed for other tardigrade species as well (Suzuki, 2003;Horikawa et al, 2008;Tsujimoto et al, 2015;Altiero et al, 2015). We have continued to focus most of our studies on Hypsibius exemplaris because of several advantages they offer over other tardigrade species for the questions we have addressed, including their clear embryos, consistently successful embryonic development in the lab, and their short and consistent embryonic development period and generation time (Goldstein, 2018;Yoshida et al, 2019). Still, some other tardigrade species offer some attractive features including even more compact genomes, a constitutive production of some protectants that contribute to survival in extremes, and an availability of males that might make classical genetics possible (Ramazzotti and Maucci, 1995;Suzuki, 2008;Bemm et al, 2017;Yoshida et al, 2017).…”
Section: Raising Hypsibius Exemplaris Cultures In a Labmentioning
confidence: 99%
“…For culturing Ramazzottius varieornatus, 2% Bacto agar (Difco) gel, Volvic mineral water, and C. vulgaris algae were used. Animals were transferred to new petri dishes every week, and eggs and juveniles were examined to study life-history traits (27). Tumanov cultured Hypsibius pallidoides for a redescription study.…”
Section: Introductionmentioning
confidence: 99%